FENOMENA BULLYING DI SEKOLAH DASAR NEGERI DI SEMARANG: SEBUAH STUDI DESKRIPTIF - Siswati, Siswati; Widayanti, Costrie Ganes (Faculty of Psychology, Diponegoro University, 2009)
The aim of this research is to identify the precentage of students who are suffered from bullying and to describe the forms of bullying in SD Negeri Semarang. The research is conducted by using questionnaire and interview with cluster sampling method. The total sample of this research is 78 students from grade 3 to 6. The result shows thar 37.55% students become victims of bullying. 42.5% students suffered from physical bullying and 34.06 yo from non physical bullying. The research also describes that there is a chance for victims to be developed as the doers. There is a low understanding from school community about bullying. Recognition and prevention about bullying have to be noticed in order to create safe place for students to be fully developed.